Chemistry. - Fantini, Jordan, ....-; Fay, Robert C., 1936-; McMurry, John E., 1942- (Boston : Prentice Hall, 2012)
When you see the connections, you'll see the chemistry. Today's students use textbooks differently than in the past; and Chemistry, Sixth Edition is designed to map to the way you seek and process information. This book is known for a smart, precise presentation that blends the quantitative and visual aspects of general chemistry. Features like Remember., Conceptual Problems, Conceptual Worked Examples, Inquiry and Worked Examples make these critical connections clear and visible, so you'll really see the chemistry the first time.